Intention toward the continuation of female genital mutilation in Bale Zone, Ethiopia - Bogale D; Markos D; Kaso M (Dove Medical Press, 2015)
Daniel Bogale,1 Desalegn Markos,2 Muhammedawel Kaso1 1Department of Public Health, 2Department of Nursing, College of Medicine and Health Sciences, Madawalabu University, Bale Goba, Ethiopia Background: Female genital mutilation (FGM) is a harmful traditional practice that is deeply rooted in Africa. It is associated with health complications and human rights violations. Research on intention for the continuation of FGM and the social determinants underpinning this practice are scarce. Therefore, this study intended to assess the intention of women toward the continuation of FGM among Bale Zone reproductive-age women.Methods: A community-based cross-sectional study design supplemented by qualitative methods was conducted in 2014. A total of 634 reproductive-age women were involved in the quantitative part of the study. The respondents were drawn from five randomly selected districts of Bale Zone. The total sample was allocated proportionally to each district based on the number of reproductive-age women it has. Purposive sampling method was used for qualitative study. Then, data were collected using a pretested and structured questionnaire. The collected data were analyzed by Statistical Package for Social Sciences for Windows version 16.0. Multiple logistic regressions were carried out to examine the existence of a relationship between intentions for the continuation of FGM and selected determinant factors.Results: This study revealed that 26.7% of the respondents had intention for the continuation of FGM. Religion, safeguarding virginity, tradition, and social values were the major reasons for the perpetuation of this practice. Circumcised respondents and those who were not able to read and write were ~3 (adjusted odds ratio = 2.89, 95% confidence interval = [1.33, 6.20]) and 7.58 (adjusted odds ratio = 7.58, 95% confidence interval = [3.47, 16.54]) times more likely intending the continuation of FGM than uncircumcised and those who attended secondary-level education and above, respectively.Conclusion: The study shows that the intention toward the persistence of the practice is high in Bale Zone. Rural residents, those who were not able to read and write, and circumcised respondents were more likely to continue the practice. Keywords: females’ genital mutilation, intention, continuation, Bale Zone